The occurrence of multidrug-resistant Mycobacterium tuberculosis from patients of pulmonary tuberculosis - Azhar Iqbal; Muhammad Shafique; Muhammad Asif Zahoor; Saima Muzammil; Zeeshan Nawaz; Abdul Jabbar; Mohsin Khurshid; Riaz Hussain; Md. Akhttarul Islam; Ahmad Almatroudi; Khaled Saleh Allemailem; Muhammad Hidayat Rasool; et al. (Journal of Infection in Developing Countries)
Introduction: Multidrug-resistant Mycobacterium tuberculosis (MDR-TB) is one of the leading causes of death in the world. The resource constraints make it difficult to diagnose and monitor the cases of MDR-TB. GeneXpert is a recognized tool used to diagnose the patients of pulmonary tuberculosis in clinical settings across the globe.